USSR and Contemporary USA: Two Paradigms of the Social Development Deadlock - K. A. Kaveev (Управленческое консультирование)
This article contains reflections of the author about two essentially different approaches by the ways of historical social development: liberal and socialist, each of which has provided social progress on a certain interval of time, at the same time, in process of realization and in different degree, each of them was deadlock. The author claims that without consideration of features and specific conditions of historical development of the countries, instilment of the way of social development, brings eventually to the deadlock. The author believes that only following to the natural course of social development of the concrete countries, without his artificial acceleration and taking into account positive experience what offers concrete way, the social progress of the concrete country and state can be provided.